S139. A retrospective study of patients with chronic inflammatory demyelinating polyneuropathy (CIDP): Identifying ultrasonographic features for diagnosis and prognosis. (May 2018) - Crump, Nicholas; Cartwright, Michael
Abstract : Introduction: CIDP often requires continued treatment over years to control the disease, with treatment decisions often made on global impression of benefit or failure rather than more formalized measures. High frequency ultrasound of peripheral nerves has the potential to provide information about nerve function and structure, and response to treatment. These parameters can be obtained non-invasively, relatively quickly, and with minimal patient discomfort, and thus are good candidates for repeatable testing. Recent studies have confirmed that NMUS is beneficial in diagnosis of CIDP, but further research is needed to determine any role in prognosis, and whether serial assessment of CIDP patients is of benefit. We aimed to determine if parameters found on neuromuscular ultrasound (NMUS) correlate with diagnosis and clinical features in patients with CIDP. Methods: We conducted a retrospective chart review to identify patients with CIDP studied with ultrasound at Wake Forest Baptist Medical Center from January 2000 to August 2017. We extracted a standardized dataset of clinical (duration of disease, current clinical state, and treatment history), electrodiagnostic and ultrasound findings (in particular nerve size as measured by cross sectional area (CSA)) from various upper and lower limb nerves. 148 patients coded with a diagnosis of CIDP (ICD-10 G61.8 and ICD-9 357.81) who attended the WFBMC diagnostic neurology laboratory were identified and the charts reviewed. Results: Of the 148 patients, 50 adult patients had been studied with ultrasound at least once. After chart review it was determined that 21 of these patients had definite CIDP, 22 an alternate diagnosis, and 7 patients had possible CIDP but had insufficient follow up to confirm. Abnormalities on ultrasound (in particular focal nerve enlargement) were common in our CIDP cohort, with 20 of 21 subjects having at least one abnormal finding. We analyzed our data in line with previously published diagnostic scores and protocols, and differences between CIDP and not CIDP patients were clearly evident, despite the often-incomplete data acquisition in this real-world retrospective cohort (sensitivity and specificity will be presented). The findings in different clinical subtypes and distribution patterns will also be presented and discussed. Conclusion: In this real-world study of ultrasound in patients with possible CIDP, there are clear differences in ultrasound parameters between those who have CIDP compared with those who have an alternate neuropathy.